Optimizing Teacher Roles: The Implications of Removing Administrative Tasks on Teachers’ Job Satisfaction, Work-Life Balance, and Teaching Performance - Olasiman, Ma. Rizza (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of removing administrative tasks from public elementary school teachers under DepEd Order No. 02, s. 2024 on teachers’ daily work experiences, job satisfaction, work-life balance, and teaching performance in small barrio schools in the Division of Bohol during School Year 2025–2026. Anchored on Herzberg’s Job Enrichment Theory, Maslow’s Hierarchy of Needs, Self-Determination Theory, and the Theory of Performance, the study employed a convergent-parallel mixed-methods design integrating descriptive-correlational and qualitative approaches. A total of 198 teachers participated in the survey, while 10 teachers were interviewed. Data were collected using validated questionnaires, documentary analysis of IPCR ratings, and semi-structured interviews, and analyzed through weighted mean, Pearson r, and thematic analysis. Findings revealed a moderate to great extent of improvement in teachers’ daily work experiences, particularly in teaching engagement and self-management, alongside moderate job satisfaction and a nearly complete work-life balance, with productivity showing the highest improvement. Teaching performance was generally very satisfactory. Significant positive relationships were found between improvements in work experiences and job satisfaction, work-life balance, and teaching performance. Qualitative results confirmed enhanced instructional focus, reduced stress, and increased motivation among teachers. However, challenges remained due to limited administrative support in small schools. The study concluded that removing administrative tasks positively influences teachers’ well-being and performance and recommended strengthening institutional support and professional development initiatives. This study aligns with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 3 (Good Health and Well-Being) by promoting improved instructional quality, better working conditions, and enhanced teacher well-being. It contributes to educational and institutional sustainability by supporting policies that improve teacher productivity, retention, and overall school effectiveness.
Keywords: Administrative Task Removal; Job Satisfaction; Teaching Performance; Teachers’ Work-Life Balance; Work Experiences